Pola Kelekatan Anak Usia Dini pada Keluarga Bercerai dan Dampaknya terhadap Ketahanan Psikologis dalam Perspektif Pendidikan Islam - Shofia Maghfiroh (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Divorce has a significant impact on early childhood emotional development, particularly in relation to attachment patterns and psychological resilience. This study aims to describe the attachment patterns of young children in divorced families, their levels of psychological resilience, and the relationship between the two within the context of Islamic education. Using a descriptive quantitative approach, 30 divorced parents were selected through purposive sampling and completed an online questionnaire consisting of 24 items measuring attachment and 15 items measuring psychological resilience. The results indicate that 60% of children exhibit high attachment, 33.3% moderate attachment, and 6.7% low attachment; meanwhile, psychological resilience is categorized as high in 46.7% of children, moderate in 43.3%, and low in 10%. These findings suggest that the majority of children are still able to develop secure attachment and positive resilience when they receive consistent emotional support from caregivers and their social environment. This study highlights the importance of responsive parenting grounded in Islamic values, including compassion (rahmah) and Islamic caregiving principles, in supporting children’s social-emotional development. The findings contribute to Islamic early childhood education (Islamic ECE) by emphasizing the need for approaches that are sensitive to both emotional and spiritual aspects of early childhood caregiving